1998
DOI: 10.1097/00007890-199811150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Early Acute Rejection With Increased Doses of Tacrolimus in Liver Transplantation

Abstract: This pilot study suggests that increasing tacrolimus dosage could be considered as treatment against early acute rejection episodes including the severe grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Previous attempts at total steroid avoidance have generally included at least one anhepatic dose, and steroids were required to treat rejection episodes (15)(16)(17)(18)(19). Tacrolimus has been shown to effectively reverse rejection and has been used as monotherapy after early steroid withdrawal (14,20). This series demonstrates the efficacy of tacrolimus monotherapy as early as 2 weeks posttransplant in steroid-free patients and yields similar results to triple immunosuppressive protocols including steroids (21).…”
Section: Resultsmentioning
confidence: 83%
“…Previous attempts at total steroid avoidance have generally included at least one anhepatic dose, and steroids were required to treat rejection episodes (15)(16)(17)(18)(19). Tacrolimus has been shown to effectively reverse rejection and has been used as monotherapy after early steroid withdrawal (14,20). This series demonstrates the efficacy of tacrolimus monotherapy as early as 2 weeks posttransplant in steroid-free patients and yields similar results to triple immunosuppressive protocols including steroids (21).…”
Section: Resultsmentioning
confidence: 83%
“…A substantial number of acute rejections reversed under increased doses of tacrolimus without the need of steroids. The results of a French pilot study16 showed that by using increased tacrolimus doses alone, early acute rejection episodes, including the severe grade, can be resolved, while tacrolimus toxicity remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of acute rejection included intravenous solumedrol boluses (1000 mg/day for 3 days) or increased doses of Tac 15…”
Section: Methodsmentioning
confidence: 99%